The results of the comparative microbiological study of gingival fluid in restoration of partial defects of tooth crowns with different materials considering the state of periodontal tissues - Fastovets, O.O.; Shram , S.S.; Kobylyak, S.S.; Ishchenko , O.V. (Medicni Perspektivi, 2025)
Different dental restoration methods probably influence the resulting pattern of periodontal microbiocenosis. The purpose of this study was to compare the periodontal microbiota composition according to the examination of the gingival fluid in the dental restorations with different materials, taking into account the state of the periodontal tissues. All participants were divided into two research groups: persons with healthy periodontium and dental caries (n=30) and patients with generalized periodontitis, I-II degree, chronic course and dental caries (n=30); and healthy control (n=10). In the participants of the research groups, partial crown defects of the II class by Black were treated with paired restorations: on the one side – with direct composite, on the other one – indirect zirconium. Gingival fluid samples were taken before treatment and 12 weeks after. It was established that the microbial load of periodontal biofilms in carious decay against the background of periodontitis was characterized by a significant number of pathogens with a deficiency of commensals and an overgrowth of obligate anaerobes. Dental biota associated with the development of periodontitis contained such patterns as Streptococcus anginosus, Porphyromonas gingivalis, Candida albicans, Fusobacterium nucleatum, Tannerella forsythia, Aggregatibacter actinomycetemcomitans. In parodontitis, it was co-aggregation of Porphyromonas spp. with Fusobacterium spp. (p<0.05) and/or Porphyromonas spp. with A. actinomycetemcomitans (p<0.05). The cariogenic pattern was distinguished by the multiplicity of the genus Streptococcus with the predominance of Streptococcus mutans, Enterococcus faecalis, C. albicans, Peptostreptococcus spp., Enterobacterales and the absence of S. anginosus, P. gingivalis, T. forsythia and A. actinomycetemcomitans. The results of the comparative microbiological study of gingival fluid after dental restorative treatment showed that zirconium restorations had the most favorable effect on periodontal microbiocenosis, in particular, it contributed to the protection against the colonization by Porphyromonas spp., Fusobacterium spp., T. forsythia, A. actinomycetemcomitans, as well as the accumulation of commensals Streptococcus salivarius and Aerococcus viridans. So, in comparison with direct composite restorations, it was more expressed approximation of the microbial spectrum, both in the persons with healthy periodontium and in the patients with general periodontitis, to the complete healthy cohort of research participants (p<0.05), which means to eubiosis. The obtained results should be taken into account when choosing a method of restorative treatment of carious decay in patients with periodontal diseases.